2010
DOI: 10.18195/issn.0313-122x.78(1).2010.185-204
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the composition of ground-dwelling spider communities in the Pilbara bioregion, Western Australia

Abstract: -Ground-dwelling spiders were sampled at 304 quadrats in 24 survey areas chosen to represent the geographical extent and diversity of terrestrial environments in the Pilbara region of Western Australia, an area of approximately 179,000 km 2 . Only taxa that were primarily ground-dwelling and were taxonomically robust were identifi ed to species level. A total of 375 species comprising 14 families was recorded. The families Salticidae (93 species), Zodariidae (71 species) and Oonopidae (70 species) showed marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Koch (1981) proposed rainfall, temperature and possibly competition to explain the distributions of individual species, but noted that vegetation type did not appear to be very important. Durrant et al (2010) found that geological history appears to be a factor in the distribution of spiders in the Pilbara region of north-western Australia, and Guthrie et al (2010) found similar patterns for ground-dwelling beetles. In both these studies, contemporary environmental factors were also important in influencing species richness and composition.…”
Section: Introductionmentioning
confidence: 81%
“…Koch (1981) proposed rainfall, temperature and possibly competition to explain the distributions of individual species, but noted that vegetation type did not appear to be very important. Durrant et al (2010) found that geological history appears to be a factor in the distribution of spiders in the Pilbara region of north-western Australia, and Guthrie et al (2010) found similar patterns for ground-dwelling beetles. In both these studies, contemporary environmental factors were also important in influencing species richness and composition.…”
Section: Introductionmentioning
confidence: 81%
“…There may therefore be some undetected temporal effects in our data, but we believe that our design would have minimised any such effects. , we also included occurrence data from accidental captures in a systematic invertebrate sampling program using fi ve wet pits, sampling over an entire year within the bounds of the vegetation plot at every quadrat that we sampled (Durrant et al 2010;Guthrie et al 2010). This meant that we were more likely to have sampled the full assemblage of species present at a given quadrat.…”
Section: Sampling Methodologymentioning
confidence: 99%
“…Spatial heterogeneity within the Pilbara, along with the extensive surrounding deserts, suggests numerous potential physiographical and habitat barriers that may have influenced the evolutionary history of the terrestrial biota. Certainly species richness patterns of both invertebrates and vertebrate fauna have shown a strong correlation with surface type (Durrant et al ., ; Guthrie et al ., ; Doughty et al ., ). Using comparative, independent datasets of multiple taxa distributed both within and outside the Pilbara, it is possible to assess fine‐scale patterns of genetic structuring in relation to the distribution of major landscape types and geodiversity, and in doing so identify potential barriers to dispersal and other abiotic factors associated with diversification.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Chichester Plateau (comprising a major mountain range in the Pilbara), aligned geologically with the southern geological unit of the Hamersley Basin (see scenario A), is considered here as part of the broad northern Chichester subregion in the IBRA regionalization. A number of recent studies have examined invertebrate species compositional patterns in light of these subregions (Durrant et al ., ; Guthrie et al ., ; Pinder et al ., ), as well as vertebrates (Gibson & McKenzie, ; Doughty et al ., ).…”
Section: Introductionmentioning
confidence: 99%